(untitled) (Castilla. Estudios de Literatura, 2019)
The intention of the following paper is to outline the theoretical bases for the understanding of a yet unstudied category of literary omission, the principle features of which lie in the deliberate and extended subtraction of relevant narrative information by the narrator, following the aim to achieve certain aesthetic effects in the reader. Once the origins and the functioning of this mechanism will have been described, it will be possible to give life to a study on a vast family of works, within which the authors tell less compared to what they know about the story they want to narrate, while allowing the text to communicate itself ironically, by clues.